Tough, Stimuli‐Responsive, and Biocompatible Hydrogels with Very High Water Content. Issue 23 (21st September 2018) - Liu, Tianqi; Lu, Shuai; Peng, Xin; Jiao, Chen; Zhang, Jianan; Han, Mei; Wang, Huiliang
Abstract: Some marine creatures like jellyfish have gel‐like bodies consisting mostly of water (above 95 wt%). Yet, their gel‐like bodies still show quite good mechanical properties and can respond to external stimuli. Artificial hydrogels with very high water content are generally extremely weak, and hence their practical applications are strongly limited. Inspired by jellyfish, tough and biocompatible poly(vinyl alcohol)/sodium polyacrylate (PVA/PAANa) hydrogels with very high equilibrium water content (98.23–99.58 wt%) are developed. The equilibrium swollen PVA/PAANa hydrogels show good mechanical properties, with elastic modulus, tensile strength, and elongation up to 0.046 MPa, 0.14 MPa, and 206%, respectively, very close to those of jellyfish mesoglea. Moreover, the PVA/PAANa hydrogels can respond to external multi‐stimuli distinctly, such as metal cations, pH, and salts. Very impressively, the PVA/PAANa hydrogel can easily distinguish tap water from deionized water, and its detection limit of metal cations can be as low as 10 −4  mol L −1 . Cell cytotoxicity tests and in vivo biocompatibility tests prove that the PVA/PAANa hydrogels have excellent biocompatibility. The tough, stimuli‐responsive, and biocompatible hydrogels with very high water content may find a variety of practical applications in load‐bearing biomaterials, detection, sensors, and agricultural fields. Abstract : Tough and biocompatible poly(vinyl alcohol)/sodium polyacrylate (PVA/PAANa) hydrogels with very high water content (98.23–99.58 wt%) are prepared by an interpenetrating network (IPN) synthetic strategy. The tensile mechanical properties of the PVA/PAANa hydrogels are close to those of jellyfish mesoglea. Moreover, the hydrogels can respond to external multi‐stimuli distinctly, such as metal cations, pH, and salts.